If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (X + 1 + 2i)(x + 1 + 2i) = 0 Reorder the terms: (1 + X + 2i)(x + 1 + 2i) = 0 Reorder the terms: (1 + X + 2i)(1 + 2i + x) = 0 Multiply (1 + X + 2i) * (1 + 2i + x) (1(1 + 2i + x) + X(1 + 2i + x) + 2i * (1 + 2i + x)) = 0 ((1 * 1 + 2i * 1 + x * 1) + X(1 + 2i + x) + 2i * (1 + 2i + x)) = 0 ((1 + 2i + 1x) + X(1 + 2i + x) + 2i * (1 + 2i + x)) = 0 (1 + 2i + 1x + (1 * X + 2i * X + x * X) + 2i * (1 + 2i + x)) = 0 (1 + 2i + 1x + (1X + 2iX + xX) + 2i * (1 + 2i + x)) = 0 (1 + 2i + 1x + 1X + 2iX + xX + (1 * 2i + 2i * 2i + x * 2i)) = 0 Reorder the terms: (1 + 2i + 1x + 1X + 2iX + xX + (2i + 2ix + 4i2)) = 0 (1 + 2i + 1x + 1X + 2iX + xX + (2i + 2ix + 4i2)) = 0 Reorder the terms: (1 + 1X + 2i + 2i + 2iX + 2ix + 4i2 + 1x + xX) = 0 Combine like terms: 2i + 2i = 4i (1 + 1X + 4i + 2iX + 2ix + 4i2 + 1x + xX) = 0 Solving 1 + 1X + 4i + 2iX + 2ix + 4i2 + 1x + xX = 0 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + 1X + 4i + 2iX + 2ix + 4i2 + 1x + -1 + xX = 0 + -1 Reorder the terms: 1 + -1 + 1X + 4i + 2iX + 2ix + 4i2 + 1x + xX = 0 + -1 Combine like terms: 1 + -1 = 0 0 + 1X + 4i + 2iX + 2ix + 4i2 + 1x + xX = 0 + -1 1X + 4i + 2iX + 2ix + 4i2 + 1x + xX = 0 + -1 Combine like terms: 0 + -1 = -1 1X + 4i + 2iX + 2ix + 4i2 + 1x + xX = -1 Add '-4i' to each side of the equation. 1X + 4i + 2iX + 2ix + 4i2 + 1x + -4i + xX = -1 + -4i Reorder the terms: 1X + 4i + -4i + 2iX + 2ix + 4i2 + 1x + xX = -1 + -4i Combine like terms: 4i + -4i = 0 1X + 0 + 2iX + 2ix + 4i2 + 1x + xX = -1 + -4i 1X + 2iX + 2ix + 4i2 + 1x + xX = -1 + -4i Add '-2ix' to each side of the equation. 1X + 2iX + 2ix + 4i2 + 1x + -2ix + xX = -1 + -4i + -2ix Reorder the terms: 1X + 2iX + 2ix + -2ix + 4i2 + 1x + xX = -1 + -4i + -2ix Combine like terms: 2ix + -2ix = 0 1X + 2iX + 0 + 4i2 + 1x + xX = -1 + -4i + -2ix 1X + 2iX + 4i2 + 1x + xX = -1 + -4i + -2ix Add '-4i2' to each side of the equation. 1X + 2iX + 4i2 + 1x + -4i2 + xX = -1 + -4i + -2ix + -4i2 Reorder the terms: 1X + 2iX + 4i2 + -4i2 + 1x + xX = -1 + -4i + -2ix + -4i2 Combine like terms: 4i2 + -4i2 = 0 1X + 2iX + 0 + 1x + xX = -1 + -4i + -2ix + -4i2 1X + 2iX + 1x + xX = -1 + -4i + -2ix + -4i2 Add '-1x' to each side of the equation. 1X + 2iX + 1x + -1x + xX = -1 + -4i + -2ix + -4i2 + -1x Combine like terms: 1x + -1x = 0 1X + 2iX + 0 + xX = -1 + -4i + -2ix + -4i2 + -1x 1X + 2iX + xX = -1 + -4i + -2ix + -4i2 + -1x Reorder the terms: 1 + 1X + 4i + 2iX + 2ix + 4i2 + x + xX = -1 + -4i + -2ix + -4i2 + -1x + 1 + 4i + 2ix + 4i2 + x Reorder the terms: 1 + 1X + 4i + 2iX + 2ix + 4i2 + x + xX = -1 + 1 + -4i + 4i + -2ix + 2ix + -4i2 + 4i2 + -1x + x Combine like terms: -1 + 1 = 0 1 + 1X + 4i + 2iX + 2ix + 4i2 + x + xX = 0 + -4i + 4i + -2ix + 2ix + -4i2 + 4i2 + -1x + x 1 + 1X + 4i + 2iX + 2ix + 4i2 + x + xX = -4i + 4i + -2ix + 2ix + -4i2 + 4i2 + -1x + x Combine like terms: -4i + 4i = 0 1 + 1X + 4i + 2iX + 2ix + 4i2 + x + xX = 0 + -2ix + 2ix + -4i2 + 4i2 + -1x + x 1 + 1X + 4i + 2iX + 2ix + 4i2 + x + xX = -2ix + 2ix + -4i2 + 4i2 + -1x + x Combine like terms: -2ix + 2ix = 0 1 + 1X + 4i + 2iX + 2ix + 4i2 + x + xX = 0 + -4i2 + 4i2 + -1x + x 1 + 1X + 4i + 2iX + 2ix + 4i2 + x + xX = -4i2 + 4i2 + -1x + x Combine like terms: -4i2 + 4i2 = 0 1 + 1X + 4i + 2iX + 2ix + 4i2 + x + xX = 0 + -1x + x 1 + 1X + 4i + 2iX + 2ix + 4i2 + x + xX = -1x + x Combine like terms: -1x + x = 0 1 + 1X + 4i + 2iX + 2ix + 4i2 + x + xX = 0 The solution to this equation could not be determined.
| -3r+8+5r+-1= | | 5+2z=2z+6 | | 15x+5=10x | | 5x-3=-9x-7 | | 5+3(5)-(4)(5)= | | w/6=4/8 | | 50x-125= | | 4/3*3.14*7.4 | | 10+x=5(15x+2) | | 10x=15x+5 | | 1/3=-3/5u-1/2 | | 9s-1/3=3/2/3 | | 13=-1/6TH | | x^2+9x-25=0 | | 7x+4-6x=15-20 | | -0.18t=5.2 | | 2x-5=3x-1.50 | | x^20-4x^18+3x-6whenx=2 | | 4a+10a+3=a+42 | | 3/2-8/1 | | 0=2x^4+7x^3+4x^2+2x-3 | | (3x+6)*(2x-4)=94 | | 12-8=a/11 | | 216n=2/3 | | (3x+6)x(2x-4)=94 | | 5n^2+10n-85=0 | | 4(x+7)=12(x-5)+8 | | -4K+7K=3+2K-3+K | | 2/3n=216 | | 2x+2=128 | | 75-5(x-1)=13(x-1) | | 12y/-7=113 |